The quest for tolerant varieties: the importance of integrating “omics” techniques to phenotyping - Zivy, Michel; Wienkoop, Stefanie; Renaut, Jenny; Pinheiro, Carla; Goulas, Estelle; Carpentier, Sebastien (Frontiers in Plant Science, 2015)
The primary objective of crop breeding is to improve yield and/or harvest quality while minimizing inputs. The global climate change and the increasing world population are great challenges for agriculture and are calling for further improvement of crops and development of new tools for research. Significant progress has been made in molecular and genetic analysis of model plants. Is science generating false expectations? Are omics techniques including proteomics generating valuable information that can be translated into practice? The exploration of crop biodiversity and the correlation of cellular responses to stress tolerance at the plant level is currently a challenge. This viewpoint paper reviews concisely the problems one encounters when working on a crops and provides an outline of possible workflows when initiating the cellular phenotyping via “-omics” techniques (transcriptomics, proteomics, metabolomics).